(untitled) (World Science, 2020)
On the example of creative work of the International Transcarpathian sculpture symposia, the article analyzes the relationship between the structure of the artistic image, the selection of forms and the material of the symposium sculpture. The conclusions about the influence of sculptural material on the disclosure of an image that uses its natural properties as signs of its own content (pattern, texture, hue, etc.) are made. It is proved that the material does not play a primary role in form and image projection, but it often directs the artist’s opinion in a certain direction of form layout and embodiment of artistic image. Emphasis is placed on the practice of sculpture symposia and the associated technique of direct carving in stone, which have directly influenced the process of updating the image and plastic consciousness of Ukrainian artists since the second half of the 1980s.